2019
DOI: 10.1515/biol-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone exerts brain protective function by reducing the expression of AQP4, APP and Aβ proteins

Abstract: This study aims to investigate the changes of aquaporin-4 (AQP4), β-amyloid precursor proteins (APP) and β-amyloid (Aβ) in brain tissues after cerebral ischemiareperfusion injury (CIRI), and evaluate the effect of edaravone. The Middle Cerebral Artery Occlusion was used to establish CIRI in rats. Rats were divided into control, model and edaravone groups. The neurological deficits in the model group were obvious and the neurological score increased compared to the control group, while the neurological deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Li C et al found that edaravone could inhibit cell apoptosis [ 50 ]. Ren C et al determine that edaravone could reduce infarct size and brain edema, and rehabilitate neurological function [ 51 ]. TTC staining, brain water content assessment, and mNSS were utilized to assess the impact of XNJ.…”
Section: Discussionmentioning
confidence: 99%
“…Li C et al found that edaravone could inhibit cell apoptosis [ 50 ]. Ren C et al determine that edaravone could reduce infarct size and brain edema, and rehabilitate neurological function [ 51 ]. TTC staining, brain water content assessment, and mNSS were utilized to assess the impact of XNJ.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of neuroprotection of edaravone described in animal models of AD (APPswe/PS1 mice) include inhibition of Aβ aggregation, reduction in tau hyperphosphorylation and attenuation of astrocytosis (GFAP reactivity) [ 204 ]. Anti-amyloid effects and modulation of aquaporin 4 (AQP4) expression of edaravone have been tested in models of ischemia/reperfusion injury [ 205 ]. In addition, protective effects have been shown regarding perfusion with superoxide (O 2 − ) and hydroxyl radical (OH) scavengers (i.e., n-propyl gallate) in astrocytic primary cultures immersed in methylmercury-induced pro-oxidant microenvironment [ 206 ].…”
Section: Astrocytes As a Therapeutic Target: Treatment And Neuroprote...mentioning
confidence: 99%